Teleworking: Socio-Economic Impact and Perspectives - Dan-Cristian Dabija (Amfiteatru Economic)
The crisis generated by the SARS-CoV-2 virus has forced organizations on a global scale to re-think their strategies and current activities, replacing traditional work at the employer’s workplace with working from home. Thirty years ago, academic research hinted at the fact that quick technological progress would facilitate working from home for white collar workers. Recent technological developments have facilitated the quick adoption of teleworking in most work sectors, especially in the sphere of services. Work done by employees outside the employer’s workplace is frequently called teleworking, although there are various alternative concepts such as “telecommuting”, “work from home”, “remote e-working”, or “home office”. Teleworking is legislated in most states; for instance, in Romania there is Law no. 81 from 2018, “concerning regulation of teleworking”, wherein policymakers address work relations.